2019
DOI: 10.1002/ppul.24581
|View full text |Cite
|
Sign up to set email alerts
|

Post‐discharge respiratory outcomes of children with acute respiratory distress syndrome

Abstract: Objectives While long‐term sequelae of acute respiratory distress syndrome (ARDS) are well‐documented in adults, few studies reported post‐discharge respiratory complications in pediatric ARDS (PARDS) and none used the recent Pediatric Acute Lung Injury Consensus Conference (PALICC) diagnostic criteria. This study describes the respiratory symptoms, pulmonary function, and health resource use of PARDS survivors at 3 months post‐discharge. Design Retrospective study. Patient Selection Children less than 18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 24 publications
1
30
2
Order By: Relevance
“…Other pulmonary function parameters, such as PEF and MIP were also reduced by one third of the predicted value. Boucher and coworkers observed that the pulmonary function can be significantly compromised in pediatric ARDS in short follow-up period (31). In adult patients with general ARDS, the FVC can recover to 3.34 ± 0.77 and 3.78 ± 1.11 L at 1 and 6 months follow up (32), which is significantly higher than that in our study.…”
Section: Discussioncontrasting
confidence: 74%
“…Other pulmonary function parameters, such as PEF and MIP were also reduced by one third of the predicted value. Boucher and coworkers observed that the pulmonary function can be significantly compromised in pediatric ARDS in short follow-up period (31). In adult patients with general ARDS, the FVC can recover to 3.34 ± 0.77 and 3.78 ± 1.11 L at 1 and 6 months follow up (32), which is significantly higher than that in our study.…”
Section: Discussioncontrasting
confidence: 74%
“…This determination was made by consensus among the authors based on literature describing the physical and emotional outcomes of PICU patients in each category and on the authors' clinical experience. 1,[3][4][5][6][7][8][9]14,[15][16][17] We then assessed the proportion of patients who were recommended to follow-up with each provider type:…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of consensus guidelines for recommended follow‐up after a general pediatric or PICU admission, the authors determined a priori the recommended providers we would anticipate patients in each population to have follow‐up appointments with. This determination was made by consensus among the authors based on literature describing the physical and emotional outcomes of PICU patients in each category and on the authors’ clinical experience 1,3‐9,14,15‐17 For respiratory failure patients, we assessed the proportion of patients who were recommended to follow‐up with primary care, pulmonology, and physical and occupational therapy. For patients who received ECMO, we assessed the proportion of patients who were recommended to follow‐up with primary care, pulmonology, physical and occupational therapy, physical medicine and rehabilitation, and neurology. For patients with tracheostomy, we assessed the proportion of patients who were recommended to follow‐up with primary care, pulmonology, physical and occupational therapy, physical medicine and rehabilitation, and otolaryngology. For all patients with respiratory failure, we examined the impact of a comorbid condition on admission and a new morbidity at discharge on the proportion of patients who were recommended to follow‐up with primary care, pulmonology, and physical and occupational therapy. For all patients with respiratory failure, we calculated the proportion of follow‐up recommended to be completed at community care center versus tertiary care center settings for those with primary care follow‐up only, specialty care follow‐up only, and both primary and specialty care follow‐up.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations